Parent’s perception in English Language Education (Rainbow Journal, 2019)
This study pursued to examine the Nepali parents' perceptions about parental involvement in learning English language and to explore relationship between parental involvement level and variables such as parents' gender, educational background, and level of proficiency in English. A sample of 123 parents, ranging the age between 30 to 70, of the students studying at primary grade of a private school was selected for the study using the simple random and convenient sampling techniques. The study focused on the identifying the parents’ perceptions of their involvement in children’s education. T-test and ANOVA were used to analyze inferential statistics of quantitative data. Findings show that parents have a positive attitude towards parental involvement and they are generally aware of the academic and psychological aspects of education. They have a good relation with the teachers and they get involved in their children’s English language education directly and indirectly. Findings also indicated that such demographic characteristics as gender, age, occupation or level of education, generally, make no significant difference on parents’ perceptions about parental involvement. Based on the findings of the study, it is recommended among others that the parents should pay the special attention to their kids at home for better performance. And reinforcing environment plays the vital role for children.